On the mathematical content of financial literacy items - Christian Dorner (Frontiers in Education)
In light of the growing intricacy of the financial sector, there is a growing imperative for individuals to possess a robust understanding of financial principles and practices. Since the global financial crisis of 2008, a variety of financial education programmes have been introduced. It is therefore not surprising that the state of financial literacy in society is becoming a topic of great interest. For this reason, surveys have been developed to assess the level of financial education in a society. Some of the items used also seem to test mathematical proficiency. This article takes a closer look at selected financial literacy items. In more detail, it considers the mathematical content of these items, the necessity of mathematical thinking for answering the items and ideas for application-oriented teaching in mathematics that can be derived from the items. The analysis shows that a wide range of mathematical topics are addressed in the items. In most cases, there are two possible lines of reasoning to arrive at the answer, one mathematical and one economic. Unless quantification is involved, then a mathematical approach is unavoidable. The items provide a couple of ideas for financial topics that can be integrated into mathematics courses, for example risk considerations. From this perspective, mathematics teaching can be seen to support the idea of financial literacy as a cross-curricular subject.